2020
DOI: 10.3390/met10010103
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Defect Detection in Laser Powder Bed Fusion by Using Thermography and Optical Tomography—Comparison to Computed Tomography

Abstract: Among additive manufacturing (AM) technologies, the laser powder bed fusion (L-PBF) is one of the most important technologies to produce metallic components. The layer-wise build-up of components and the complex process conditions increase the probability of the occurrence of defects. However, due to the iterative nature of its manufacturing process and in contrast to conventional manufacturing technologies such as casting, L-PBF offers unique opportunities for in-situ monitoring. In this study, two cameras we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 28 publications
0
57
0
2
Order By: Relevance
“…This error diminishes once the spatial temperature gradients have decreased due to lateral heat flow. These limitations are discussed in more detail by Mohr et al [20]. Despite these limitations, qualitative analysis of the thermography data revealed results that contribute to the understanding of the presented RS results.…”
Section: Thermographymentioning
confidence: 88%
“…This error diminishes once the spatial temperature gradients have decreased due to lateral heat flow. These limitations are discussed in more detail by Mohr et al [20]. Despite these limitations, qualitative analysis of the thermography data revealed results that contribute to the understanding of the presented RS results.…”
Section: Thermographymentioning
confidence: 88%
“…Among the approaches of thermal condition monitoring, contactless measurement techniques are most common. Passive infrared (IR) thermography is a technology which was used by several groups of authors for thermal in situ process monitoring means [7,[9][10][11][12][13][14]. IR thermography can acquire data of thermal emissions of the process layer by layer with variations in spatial and temporal resolutions, depending on the particular equipment and setup [12].…”
Section: Thermal Monitoring In L-pbfmentioning
confidence: 99%
“…For example, Zenzinger et al [ 35 ] demonstrated the link between the hotspots in OT images to the defect in the μCT scan of the layer. Recently, Mohr et al [ 38 ] also studied the OT images to detect a defect in the final part and compared the OT images with the μCT images. It was also verified that the hotspots in the OT images link to defect in the final part.…”
Section: Methodsmentioning
confidence: 99%